2004
DOI: 10.1210/jc.2004-0881
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Cytotoxic T Lymphocyte-Associated Antigen 4 Gene with Type 1 Diabetes: Evidence for Independent Effects of Two Polymorphisms on the Same Haplotype Block

Abstract: A recent study mapped the known association of type 1 diabetes with the cytotoxic T lymphocyte-associated antigen 4 gene to a polymorphism at the 3'end (+6230G>A), but could not rule out additional contribution from the 5' end of the gene. To examine this possibility, we analyzed four polymorphisms at the 5'-flanking region for effects independent of +6230G>A. We confirm, by the transmission disequilibrium test, in 496 family trios overtransmission of the susceptibility allele (G) at +6230 (217/168; P = 0.013)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 46 publications
3
59
1
2
Order By: Relevance
“…We had previously reported B40% higher expression of the À318T allele vs the À318C allele in mRNA without distinguishing between full-length and soluble CTLA4 transcripts. 9 In this study, we confirm a significantly higher expression from the À318T; þ 49A; þ 6230G haplotype than À318C; þ 49G; þ 6230G in flCTLA4 transcripts, where the mean allelic ratio of A/G is 1.3670.06 (7s.e.m.) (95% CI, 1.24-1.47) vs that in genomic DNA, 1.0370.01 (7s.e.m.)…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…We had previously reported B40% higher expression of the À318T allele vs the À318C allele in mRNA without distinguishing between full-length and soluble CTLA4 transcripts. 9 In this study, we confirm a significantly higher expression from the À318T; þ 49A; þ 6230G haplotype than À318C; þ 49G; þ 6230G in flCTLA4 transcripts, where the mean allelic ratio of A/G is 1.3670.06 (7s.e.m.) (95% CI, 1.24-1.47) vs that in genomic DNA, 1.0370.01 (7s.e.m.)…”
Section: Resultssupporting
confidence: 70%
“…This effect is consistent with the independent T1D association with À318C4T but does not explain the genetic effect of þ 6230G4A. 9 Characterization of the þ 6230G4A-containing transcript In the study by Ueda et al, 5 there are two transcripts detected by Northern blot analysis in resting PBMCs: a 4.1 and 2 kb transcript. Although it is possible that the larger transcript contains the 3 0 SNP, this is not clear from this experiment.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…It has been reported that five single-nucleotide polymorphisms of the CTLA4 gene (namely À1661A/G, À658C/T, À318C/T, þ 49A/G and þ 6230A/G) are in strong linkage disequilibrium. 39 The CTLA4 À318C/T polymorphism could affect transcriptional efficiency by modifying a transcription factor binding site for LEF1, and thereby regulate CTLA4 expression. 39 Ueda et al 40 found lower CTLA4 expression levels from the G allele at the þ 6230A/G polymorphism.…”
Section: Ctla4 Gene Polymorphisms In Ucmentioning
confidence: 99%
“…39 The CTLA4 À318C/T polymorphism could affect transcriptional efficiency by modifying a transcription factor binding site for LEF1, and thereby regulate CTLA4 expression. 39 Ueda et al 40 found lower CTLA4 expression levels from the G allele at the þ 6230A/G polymorphism. Hence, the CTLA4 À1661A/G polymorphism, could be associated with UC and effect gene expression as part of a haplotype with combined effects of neighboring polymorphic markers, such as À318C/T or þ 6230A/G.…”
Section: Ctla4 Gene Polymorphisms In Ucmentioning
confidence: 99%